Comparing the contribution of formal and local seed systems to household seed security in eastern Zimbabwe - Ncube, Bulisani L.; Wynberg, Rachel; McGuire, Shawn (Frontiers in Sustainable Food Systems, 2023)
Introduction Interventions aimed at improving the seed security of smallholder farmers do not always yield positive results. Governments, donors, and other actors have neglected local seed systems as they are assumed to be incapable of addressing farmers’ seed challenges. Instead, external actors use seed aid and formal seed provisioning outlets, such as agro-input dealers, to channel seed to farmers. This paper compares the “formal” seed systems, mainly comprising certified seed obtained from government and non-governmental organisations and agro-input dealers, with local seed systems that include farm-saved seed, local informal markets, and social networks. Methods A seed security assessment was used to determine the contributions of seed systems to household-level seed security. A stratified sample was conducted of 227 randomly selected smallholder farming households from the Chimanimani district, eastern Zimbabwe, complemented by group discussions and individual life histories. Results We show the superiority of local seed systems in ensuring greater access to affordable and timely seed at household level, in comparison to formal sources. Cluster analysis enabled determination of the seed security status of farming households, providing a more granular analysis beyond the standard seed security assessments that are applied to wider geographical locations. Farmers assessed the quality of locally sourced seed favourably when compared to seed obtained from formal sources. Discussion We show that local seed systems play a critical role in contributing to household seed security for resource-constrained households, and in supporting the use of diverse crop species. However, such systems have not been fully drawn upon by government and development agencies in seed security endeavours. More efforts are needed to understand how different seed systems interact in contributing to the seed security of smallholder farming households.